Pengolahan Ampas Tahu Sebagai Pakan Alternatif Untuk Ikan Bandeng Di Desa Kedung Sekar Kecamatan Benjeng Kabupaten Gresik - Heri Susanto (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
The tofu dregs processing is carried out to provide training in the use of tofu waste for milkfish cultivation which aims to (1) process waste into tofu-based feed (2) feed milkfish derived from organic ingredients so that the milkfish will develop well (3 ) Providing efficiency in the cost of milkfish cultivation has an impact on the income of pond farmers. The method applied is Agribusiness Integrated utilization of tofu waste based on soybeans to be used as fish feed / organic milk pellets. Considering the abundance of tofu waste which is not processed and does not have a selling value, after processing it becomes a pellet having a selling value from the production cost of the price of Rp. 5000 / kg compared to the price of milkfish pellets in the market reaching Rp. 12,000 - Rp. 18,000 / kg. With this alternative feed processing, it can reduce the cost of milkfish cultivation by more than 60%, with the cost of per hectare requiring 600 Kg / hapakan with an average price of Rp. 15,000 to a total cost of Rp. 9,000,000 / ha after the utilization of tofu waste has a cost of Rp. 3000,000 / ha. Besides that, this community service can contribute a little to contributing to the government program, which is a waste-free community.